2022
DOI: 10.1002/14651858.cd010130.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers as point-of-care tests to guide prescription of antibiotics in people with acute respiratory infections in primary care

Abstract: Biomarkers as point-of-care tests to guide prescription of antibiotics in people with acute respiratory infections in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 129 publications
(11 reference statements)
3
17
0
Order By: Relevance
“…In line with findings from primary care practices,11 12 our results indicate that point-of-care CRP testing may have the potential to reduce antibiotic prescriptions in OEMS, which is especially important under the light of the rise of antibiotic resistance. The result of our study are also consistent with another primary care study showing that clinicians perceive that CRP-POCTs increase confidence, reduce diagnostic uncertainty and facilitate communication between patients and clinicians 34.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In line with findings from primary care practices,11 12 our results indicate that point-of-care CRP testing may have the potential to reduce antibiotic prescriptions in OEMS, which is especially important under the light of the rise of antibiotic resistance. The result of our study are also consistent with another primary care study showing that clinicians perceive that CRP-POCTs increase confidence, reduce diagnostic uncertainty and facilitate communication between patients and clinicians 34.…”
Section: Discussionsupporting
confidence: 79%
“…CRP has a diagnostic value (although limited in some cases) in differentiating between bacterial and viral infections9 as well as estimating the severity of bacterial infections 10. POCT measurement of CRP has been shown to safely reduce antibiotic prescriptions in respiratory tract infections (RTI) in primary care settings11 12 as well as in nursing homes 13. There is also evidence that CRP-POCTs can improve antibiotic prescriptions14 and shorten the length of stay in emergency medical services 15–17.…”
Section: Introductionmentioning
confidence: 99%
“…23 A Cochrane review on the subject found that CRP POCT testing for ARTIs in general practice can reduce antibiotic use, and the intervention is unlikely to increase morbidity. 20 We aim to study if CRP POCT testing in primary care can safely reduce antibiotic use in children with ARTI in Kyrgyzstan.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“… 19 Randomised trials of using CRP point-of-care test (POCT) to guide antibiotic prescription for respiratory tract infections have been successful in lowering unnecessary antibiotic prescriptions in high-income countries and some LMIC countries. 20 21 Trials of CRP POCT in children have been performed in Tanzania as part of an intervention package with a strict prescription limit of >80 mg/L CRP with a significant reduction in antibiotic prescriptions from 40% to 2%. 21 In South-East Asia, a CRP intervention produced a smaller but significant effect (5%) in children and adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation